2017
DOI: 10.1107/s2052252517004043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis ofN-salicylideneaniline: thermosalient effect of polymorphic crystals

Abstract: Among the halogen derivatives of N-salicylideneaniline, polymorphs of the dichloro compound A showed the mechanical response of jumping (Forms I and III) and sudden blasting (Form II) upon heating. This difference is ascribed to the layered packing in Forms I and III such that the thermal stress acts in a unidirectional manner while for the corrugated layer structure of Form II the outcome is blasting because the thermal energy dissipates in different directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…The effect was first noted in 1983, and after a long hiatus, it was explored in greater detail in the anticholinergic agent oxitropium bromide in 2010 . Encouraged by these studies, over 20 new examples have been reported in the last decade that are categorized in three classes based on their structures, with a number of notable reports of serendipitous observations increasing in the past several years . It has also been demonstrated that the rates of the TS phase transitions are several orders of magnitude faster than other, more common solid–solid transitions .…”
Section: Introductionmentioning
confidence: 99%
“…The effect was first noted in 1983, and after a long hiatus, it was explored in greater detail in the anticholinergic agent oxitropium bromide in 2010 . Encouraged by these studies, over 20 new examples have been reported in the last decade that are categorized in three classes based on their structures, with a number of notable reports of serendipitous observations increasing in the past several years . It has also been demonstrated that the rates of the TS phase transitions are several orders of magnitude faster than other, more common solid–solid transitions .…”
Section: Introductionmentioning
confidence: 99%
“…The meltw as cooled, and the solid material also movedw hile solidifying. [2][3][4][5][6][7][8][9][10][11] In contrastwith form I, crystals of form III did not show motion, as determined by HSM, and thus, this polymorph was determined not to be thermosalienta bove room temperature. Af ew crystals that did not jump melted at ah igher temperature ( Figure 1B).…”
Section: Resultsmentioning
confidence: 90%
“…As no chemical decomposition such as evolution of gas could be observed, this behavior was ac lear signature of the thermosalient effect, ap henomenon by which crystals acquire momentum and move or burst owing to sudden release of the elastic energy accumulated during af irst-order,m artensitic-like phase transition. [2][3][4][5][6][7][8][9][10][11] In contrastwith form I, crystals of form III did not show motion, as determined by HSM, and thus, this polymorph was determined not to be thermosalienta bove room temperature. Regrettably,f urther thermal and microscopy characterization of crystalso ff ormII, the disappearing polymorph of 2,was not possible owing to their paucity.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…1) by Mittapalli et al, reported in this issue of IUCrJ, revealed four polymorphs, three of which exhibit mechanical responses such as jumping (forms I and III) and exploding (form II) during phase transition at high temperature (Mittapalli et al, 2017). This is a rare example of a combination of mechanophysical responses in polymorphs of the same compound (Steiner et al, 1993;Crawford et al, 2007;Sahoo et al, 2013).…”
mentioning
confidence: 99%